The reluctant heiress - Richardson, Evelyn (U.S.A. : Signet Book Penguin Books, 1996)
Lady Sarah Melford was quite happy to live inthe shadow of her elder brother, the Marques of Cranleigh, and his dazzlingly beautiful wife, Rosalind.
Capter one Chapter two Chapter three Chapter four Chapter five and others twenty six chapters more thirty-01
Keywords: ENGLISH LITERATURE; ROMANTIC STORY